2x-0.3-2.6x=3.42

Simple and best practice solution for 2x-0.3-2.6x=3.42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-0.3-2.6x=3.42 equation:


Simplifying
2x + -0.3 + -2.6x = 3.42

Reorder the terms:
-0.3 + 2x + -2.6x = 3.42

Combine like terms: 2x + -2.6x = -0.6x
-0.3 + -0.6x = 3.42

Solving
-0.3 + -0.6x = 3.42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.3' to each side of the equation.
-0.3 + 0.3 + -0.6x = 3.42 + 0.3

Combine like terms: -0.3 + 0.3 = 0.0
0.0 + -0.6x = 3.42 + 0.3
-0.6x = 3.42 + 0.3

Combine like terms: 3.42 + 0.3 = 3.72
-0.6x = 3.72

Divide each side by '-0.6'.
x = -6.2

Simplifying
x = -6.2

See similar equations:

| 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 | | 66*10= | | 8x-(6x+7)=6x-47 | | ×/11=×/12-8 | | 6+8-78738+3837484849=0939v | | 5x-40=10x-50 | | 6x-7-x=17 | | 58800=P-(0.00917P) | | -12=m+1-6 | | -7x-33=-9x+25 | | x+.10=70 | | =14*2.8+21*4.2 |

Equations solver categories